Proceedings of the 2017 CHI Conference on Human Factors in Computing Systems 2017
DOI: 10.1145/3025453.3025518
|View full text |Cite
|
Sign up to set email alerts
|

Audible Beacons and Wearables in Schools

Abstract: Young children with visual impairments tend to engage less with their surroundings, limiting the benefits from activities at school. We investigated novel ways of using sound from a bracelet, such as speech or familiar noises, to tell children about nearby people, places and activities, to encourage them to engage more during play and help them move independently. We present a series of studies, the first two involving visual impairment educators, that give insight into challenges faced by visually impaired ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(5 citation statements)
references
References 26 publications
(55 reference statements)
0
5
0
Order By: Relevance
“…In applications like these, where the time or length of speech does not make a significant difference, the audio-based systems are less cognitively demanding and serve the purpose. Studies have found that audible beacons and wearables can be a great way to enhance the independent movement and playing of young VI children (Freeman et al, 2017). This study identifies ways to integrate environmental sound with the sound of wearables that also helps in proximity estimation between objects.…”
Section: Overviewmentioning
confidence: 99%
“…In applications like these, where the time or length of speech does not make a significant difference, the audio-based systems are less cognitively demanding and serve the purpose. Studies have found that audible beacons and wearables can be a great way to enhance the independent movement and playing of young VI children (Freeman et al, 2017). This study identifies ways to integrate environmental sound with the sound of wearables that also helps in proximity estimation between objects.…”
Section: Overviewmentioning
confidence: 99%
“…The approach of mainstream education for visionimpaired students instead of special schools [20] is accompanied by persistent issues in participation [21,22] and limited chances for collaboration and social interaction [23,24]. The design of assistive learning technologies usually concentrates exclusively on the needs of vision-impaired students, thereby disturbing inclusive learning experiences for their sighted peers [25].…”
Section: Educational Robotics and Human-robot Interaction Role In Inc...mentioning
confidence: 99%
“…A solution to enhance spatial awareness is in using auditory cues. For example Freeman et al used remote audio devices to improve orientation and navigation for VI, where the indicative audio would be played at fixed locations as 'reference sounds' [14]. It is furthermore observed that spatial awareness training that is done in simulated environments such as VR is directly transferable to real life [15].…”
Section: Related Workmentioning
confidence: 99%